Transient contour of bioprosthetic heart valve leaflet : an experimental and numerical investigation - Ke, Li (2009)
Understanding the transient contour of the mechanical behavior in the bioprosthetic heart valve is essential to realize the optimal design of BHV. This PhD project aims to develop FE model by adding more physiological data from experiment to supplement the deficient loads. An experimental technique was developed using an optical and image processing techniques to track the transient contour of the moving valve leaflet. A dual-camera stereo photogrammetry technique is used to retrieve the 3-D coordinates of the marker matrix drawn on the leaflet surface via pairs of instantaneous digital images during a complete valve opening and closing cycle. The reconstructed 3-D locations during the cardiac cycle were used as dynamic boundary conditions in a numerical leaflet model. Current simulation shows more accurate physiological deformation and will help for further stress understanding of the leaflet.